PENGARUH KINERJA SUMBER DAYA MANUSIA TERHADAP KINERJA PROYEK KONSTRUKSI DI KABUPATEN BADUNG - Dharmayanti, Gusti Ayu Putu Candra; Adnyana, Ida Bagus Rai; Nugraha, Made Arditya (Jurnal Ilmiah Teknik Sipil, 2020)
The construction workers are identical with hard sector work that gives challenges in managing them . The project human resources play an important role contributing to the project success , therefore there is a need to further examine the indicator of human resources performance that dominant ly influence the project performance. T his research aimed to examine the influence of human resources performance indicators towards the construction project performance, in Badung Regency. Data collection was conduted through a survey using questionnaires that was distributed to 50 respondents selected based on purposive sampling metho d that covered project manager, site manager, site engineer, quantity surveyor, quality control, drafter, programmer, supervisor, and logistics. Data were anal yzed using multiple linear regression analysis, multiple correlation analysis, determination test, and t test. The result of multiple linear regression analysis proved that the construction project performance was influenced by human resources performance . The value of determination test (0.886) indicate d that there was a strong and positive correlation between discipline, initiative, training, motivation, quality, working environment, commitment, responsibility, and tools , toward the project performance . The value of t- tes t of of each human resources performance indicato r were discipline (3,863), initiative (-1,515), training (-1,252), motivation (0,598), quality (-1,164), working environment (1,655), commitment (2,169), responsibility (-2,958), ability (3,822), and tools (3,439). These suggested that discipline was the most dominant indicator in influencing the project performance.